LATIHAN DUMBELL WRIST CURL DAN LATIHAN MEDICINE BALL CHEST PASS DAPAT MENINGKATKAN KEMAMPUAN SHOOTING PADA ATLET BHAYANGKARA BASKET CLUB TAHUN 2020 - Ridho Agus Rahmansyah; Muhammad Ridwan Lubis; Sri Erny Mulyani (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2020)
The background of this research is that the players in shooting are less focused, precise and strong. This is what motivates the researchers to try to apply the dumbell wrist curl and medicine ball chest pass exercises to improve strength and ability to shoot. This study aims to determine which form of exercise has a greater influence between dumbbell wrist curl and medicine ball chest pass training on shooting ability of Bhayangkara Basket Club athletes in 2020. The research method used was experimental. The total sample of 16 athletes obtained by total sampling technique, then divided into two groups, namely the dumbbell wrist curl exercise group and the medicine ball chest pass exercise group. The research was conducted by testing and measuring the basketball shooting test for Bhayangkara Basket Club athletes in 2020, which was carried out 6 weeks 18 (eighteen) times of training. Furthermore, the research data was processed by statistical calculation of paired and unpaired t-test. Based on the results of the paired t-test calculation of hypothesis I, the t-count value is 3.989 and 〖t〗 _ (table) with dk n-1 = 7, at the 5% significance level is 1.895. Thus t_h> t_ (t) so that H_o is rejected and H_a is accepted. Conclusion: There is a significant effect of dumbbell wrist curl training on the shooting ability of Bhayangkara Basket Club athletes in 2020. From the results of the paired t-test for hypothesis II, the t-test value is 4,964 and t-table dk n-1 = 7, at the 5% significance level. is 1,895. Thus t_h> t_ (t) so that H_o is rejected and H_a is accepted. Conclusion: There is a significant effect of medicine ball chest pass training on the shooting ability of Bhayangkara Basket Club athletes in 2020. From the results of the unpaired t-test for hypothesis III, the value of tcount = 0.722 and t table = 1.761. Thus t_h <t_ (t) so that H_o is rejected and H_a is accepted. Conclusion: that the dumbell wrist curl exercise has no greater effect than the medicine ball chest pass exercise on the shooting ability of Bhayangkara Basket Club athletes in 2020